Métodos Simples De Armazenamento Das Sementes De Andiroba (Carapa Guianensisaubl. E Carapa Procerad.C. -Meliaceae). - Ferraz, Isolde Dorothea Kossmann; Sampaio, Paulo de Tarso Barbosa (Acta Amazonica, 1996)
It was intended to test several simple storage methods, which could be wildly used to conserve recalcitrant seeds of forest trees, whose reforestation is limited by the shortage of its seeds. Carapa procerae C. guianensisare tropical trees of economic interest, its seeds loose viability few days after collection. It was already shown, that for C. procera this loss of viability is correlated with the moisture content of the seeds. The storage of the seeds in plastic bags were studied during 7 months under different environmental conditions and in water. The moisture content of the seeds was observed before and after the storage. Storage under external conditions was not successful, probably because the plastic bags were destroyed by insects which caused dehydration of the seeds, or hydration of those stored in the soil, which then consequently started to germinate. Storage under current water was not possible; neither storage at low temperature (6 °C +/- 4 °C). It was possible to maintain the viability of the seeds in sealed plastic bags under air conditioning (25°C +/- 4 °C and 45 - 60% r. H.) during 7 months.
Simple Storage Methods for Andiroba Seeds (Carapa guianensisAubl. e Carapa proceraD. C. - Meliaceae).
Keywords: Carapa Procerad. Ο; Carapa Guianensisaubl; Seed Storage; Recalcitrant Seeds; Carapa Procera D.C.; Carapa Guianensis Aubl.; Armazenamento de sementes; Sementes Recalcitrantes